Does commuting matter to subjective well-being? - Olga Lorenz (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
How and why commuting contributes to our well-being is of considerable importance for transportation policy and planning. This paper analyses the relation between commuting and subjective well-being by considering several cognitive (e.g., satisfaction with family life, leisure, income, work, health) and affective (e.g., happiness, anger, worry, sadness) components of subjective well-being. Fixed-effects models are estimated with German Socio-Economic Panel data for the period 2007 - 2013. In contrast to previous papers in the literature, according to which commuting is bad for overall life satisfaction, we find no evidence that commuting in general is associated with a lower life satisfaction. Rather, it appears that longer commutes are only related to lower satisfaction with particular life domains, especially family life and leisure time. Time spent on housework, child care as well as physical and leisure activities mediate the association between commuting and well-being.
Keywords: I10; I31; R40; 330; commuting distance; emotion; satisfaction; time use; well-being